The Choice of Prices vs. Quantities under Uncertainty - Markus Reisinger; Ludwig Ressner (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
If duopolistic firms can choose their strategy variable, uncertainty about demand conditions and the degree of substitutability have countervailing effects on variable choice. High uncertainty favors prices, while close substitutability favors quantities. For intermediate values, a hybrid equilibrium exists.
Keywords: D43; L13; 330; Competition; Strategy Variables; Demand Uncertainty